Civil Resistance against Totalitarian Regime in the Movie Truth and Treason: A Semiotic Analysis - Akbar Adiwinata; Syamsurrijal Syamsurrijal; Abdul Muhid (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
A totalitarian regime is a system of power that seeks to control various aspects of people's lives through propaganda, discrimination, and restrictions on individual freedoms. This condition often gives rise to various forms of civil resistance in response to oppressive practices carried out by the state. This study aims to identify the representation of civil resistance against a totalitarian regime in the movie Truth and Treason through Roland Barthes' semiotic approach. This study uses a qualitative method with semiotic analysis techniques that focus on three levels of meaning: denotation, connotation, and myth. The results show that civil resistance is represented through three main forms: (1) rejection of national identity, (2) rejection of discrimination, and rejection of restrictions on freedom of expression. This study concludes that civil resistance is not always manifested through physical action or direct confrontation, but can also be represented through symbolic and non-violent actions that convey the meaning of rejecting injustice. As the results, the movie Truth and Treason demonstrates that moral courage, human solidarity, and freedom of thought can be effective forms of resistance in the face of the domination of totalitarian regimes.